The m6A methyltransferase METTL3 promotes LPS-induced microglia inflammation through TRAF6/NF-κB pathway. Issue 6 (6th November 2020) - Wen, Linbao; Sun, Wei; Xia, Dayong; Wang, Yanming; Li, Junpeng; Yang, Song
Abstract : Objectives: Microglia are the main effectors in the inflammatory process of the central nervous system. Once overactivated, microglia may release pro-inflammatory cytokines (IL-1β, IL-6, TNF-α and IL-18, etc.) and accelerate neurodegeneration. Here, we aimed to explore the mechanism of how m6A methyltransferase METTL3 affects the inflammatory response of microglia, appropriately inhibiting the overactivation of microglia. Materials and methods: Lipopolysaccharide (LPS) was used to construct a cellular inflammation model in vitro . To evaluate the expression of METTL3 and inflammatory cytokines (IL-1β, IL-6, TNF-α and IL-18) in cells, RT-PCR and ELISA were carried out. The related protein (TRAF6, NF-κB and I-κB) expression was examined adopting Western blot. Dot blot experiment was used to assess the effect of regulating METTL3 on the m6A level. Methylated RNA immunoprecipitation reaction was used to measure the effect of METTL3 on the m6A level of TRAF6 mRNA 3′-UTR. The co-immunoprecipitation experiment (IP) proved that METTL3 combines with TRAF6. Results: In LPS-mediated microglial inflammation, METTL3 expression was increased, and the expression of inflammatory cytokines (IL-1β, IL-6, TNF-α and IL-18) and inflammatory proteins (TRAF6 and NF-κB) were upregulated. METTL3 level was positively correlated with TRAF6, and the two proteins could bind to each other. Overexpression of METTL3 promoted the activation of the TRAF6-NF-κB pathway in an m6A-dependent manner, and inhibiting NF-κB attenuated METTL3-mediated microglial activation. Conclusion: METTL3 promotes LPS-induced microglial inflammation by activating the TRAF6-NF-κB pathway.